The role of moral decoupling in the causes and consequences of unethical pro-organizational behavior - Fehr, Ryan; Welsh, David; Yam, Kai Chi; Baer, Michael; Wei, Wu; Vaulont, Manuel (Organizational behavior and human decision processes, 2019)
•The role of leader moral decoupling in employee UPB is examined.•Perceptions of leader moral decoupling are shown to shape employee UPB.•Leader moral decoupling is shown to shape leader reactions to employee UPB.•Implications for theory and practice are discussed. In this paper we explore the antecedents and consequences of employees’ unethical pro-organizational behavior (UPB) through the lens of moral decoupling—a moral reasoning process whereby individuals separate their perceptions of morality from their perceptions of performance. First, we argue that employees increase their engagement in UPBs when they (1) see their supervisors doing the same and (2) believe that their supervisors endorse moral decoupling. Second, we argue that employees’ UPBs are only positively related to supervisors’ evaluations of their job performance when supervisors themselves report that they morally decouple. We test these hypotheses in a field sample of supervisor–employee dyads and two experimental studies. This combination of studies highlights the complex link between ethics and perceptions of performance within organizations.